Surface engineering of nanoporous anodic aluminium oxide for biosensor application in the detection of dengue virus type II / Abdul Hadi Mahmud - Mahmud, Abdul Hadi (2017)
In this work, nanoporous anodic aluminium oxide (AAO) membrane-based optical biosensor was constructed for targeting the DNA Dengue virus type II. The AAO membrane was fabricated by electrochemical anodization of aluminium foil applying different voltages from 40-100 V. To increase the sensitivity of the biosensor device, amino (l-propyl-4,5-dihydro-lH-l,2,3-triazol-4-yi)-triethoxysilane (click compound) was synthesized and introduced on to the AAO by silanization approach followed by l-ethyl-3-[3-dimethylaminopropyl] carbodiimide (EDC) mediated immobilization of amino (Nty-modified probe ssDNA. Fluorescent-tagged (Texas red) complementary target DNA was used for DNA hybridization process on modified AAO. Characterization of the AAO membrane's morphology was observed by means of Field Emission Scanning Electron Microscope (FE-SEM)